Handbook of Fuel Cells 2010
DOI: 10.1002/9780470974001.f205038
|View full text |Cite
|
Sign up to set email alerts
|

Fundamental kinetics/transport processes in MEAs

Abstract: The results of fundamental and applied research on the development of dispersed catalysts, gas‐diffusion electrodes and membrane and electrode assemblies (MEAs) for polymer electrolyte fuel cells (PEFCs) are discussed. In the first part, the electrocatalysis of the oxygen reduction reaction on dispersed platinum catalysts used for the preparation of fuel cell electrodes is briefly considered. The issue is analyzed mainly in terms of the size and structure of the catalyst particles. Next, efforts on the develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
2

Year Published

2013
2013
2013
2013

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 55 publications
0
1
0
2
Order By: Relevance
“…Nart et al (2009) have noticed that in catalysis, the important parameter is the active surface area, which is given by the active material [19]. Than Ticianelli et al (2010) have renowned that for such applications, in order to provide the best performance with minimum content of platinum, the most important metallic material employed for the catalysis, one cm 2 of the active surface area contain a value of 2 mg of the noble metal catalyst load, can be maximised for supporting about 20 mg of Pt [20] and Ünlü et al (2010) have noticed that it is more difficult to determine the true surface area in a particular operating fuel cell than the superficial area, even they observed the decrease in the active area by flooding due to faster water generation at high current densities and the charge-transfer resistance consists of a purely kinetic term and is inversely proportional to the active surface area [21]. Ho et al (2011) have revealed a new catalyst support, featuring can give a progress: a high surface area and high proton conductivity, efficiency and durability of polymer electrolyte membrane fuel cells [22], Zakrisson (2011) reported that the platinum is expensive and contributes to a large extent to the high price of PEM fuel cells, which makes it desirable to use the platinum as effective as possible.…”
Section: Introductionmentioning
confidence: 99%
“…Nart et al (2009) have noticed that in catalysis, the important parameter is the active surface area, which is given by the active material [19]. Than Ticianelli et al (2010) have renowned that for such applications, in order to provide the best performance with minimum content of platinum, the most important metallic material employed for the catalysis, one cm 2 of the active surface area contain a value of 2 mg of the noble metal catalyst load, can be maximised for supporting about 20 mg of Pt [20] and Ünlü et al (2010) have noticed that it is more difficult to determine the true surface area in a particular operating fuel cell than the superficial area, even they observed the decrease in the active area by flooding due to faster water generation at high current densities and the charge-transfer resistance consists of a purely kinetic term and is inversely proportional to the active surface area [21]. Ho et al (2011) have revealed a new catalyst support, featuring can give a progress: a high surface area and high proton conductivity, efficiency and durability of polymer electrolyte membrane fuel cells [22], Zakrisson (2011) reported that the platinum is expensive and contributes to a large extent to the high price of PEM fuel cells, which makes it desirable to use the platinum as effective as possible.…”
Section: Introductionmentioning
confidence: 99%
“…O mais comum é a classificação baseada na natureza do eletrólito e, desta forma, temos cinco principais tipos de células, conforme ilustrado na Tabela 1. 4,6,7 Outras pesquisas apontam ainda a possibilidade de utilizar etilenoglicol e glicerol. 8,9 Dentre os principais combustíveis, o H 2 apresenta maior densidade de potência e menor polarização anódica frente aos alcoóis leves.…”
unclassified
“…Stackpole ® ) e uma suspensão de politetrafluoretileno (PTFE -Teflon T-30, DuPont ® )[14,53]. Para a sua preparação, inicialmente foi feito um tratamento térmico do tecido de carbono a 450°C em atmosfera ambiente e, em seguida, durante o tempo de 1h, foi tratado com uma solução de ácido nítrico 25% V/V a 80°C, diminuindo assim o seu caráter hidrofílico.…”
unclassified